Regionalization of health surveillance: a performance evaluation proposal in a health region in Brazil - Ana Coelho de Albuquerque; Eduarda Ângela Pessoa Cesse; Eronildo Felisberto; Isabella Samico; Liza Yurie Teruya Uchimura; Nathalie Estima
Abstract Objectives: To evaluate the performance of the regionalization of the Vigilância em Saúde (VS) (Health Surveillance) in a region in Sao Paulo State. Methods: a quantitative cross-sectional study was carried out at the V Diretoria Regional de Saúde da Secretaria de Saúde do Estado de São Paulo (V Board of the Regional Health Secretary of São Paulo State Health Department). A structured questionnaire was developed from the three dimensions of the research (Policy, Structure and Organization). The escore médio (EM) (average score) was used as the central tendency and for each dimension and attributes, the synthetic indices were constructed. Three cutoff points for assessing the performance were assigned: values equal to or below 4.99 were considered unsatisfactory; between 5.00 and 6.99, intermediaries; and equal to or above 7.00, satisfactory. Results: The performance of the regionalization of the VS was considered satisfactory, with emphasis on the 'Policy' (EM 8.51) and 'Organization' (EM 8.18) dimensions. The 'Structure' obtained intermediate performance (EM 6.78). The proposed methodology demonstrated to be appropriate to evaluate the performance of the regionalization of VS, because its strengths and weaknesses were allowed to be identified. Conclusions: despite of the regionalization is an ongoing process, it is necessary for the establishment of a political project that will take up effectively as a strategy for the reorganization of the healthcare in Brazil.